miR-22-3p Suppresses Endothelial Progenitor Cell Proliferation and Migration via Inhibiting Onecut 1 (OC1)/Vascular Endothelial Growth Factor A (VEGFA) Signaling Pathway and Its Clinical Significance in Venous Thrombosis - Liang, Huoqi (Med Sci Monit, 2020)
BACKGROUND: Proliferation and migration play crucial roles in various physiological processes, especially in injured endothelial repair. Endothelial progenitor cells (EPCs), as the precursors of endothelial cell, are involved in the regeneration of the endothelial lining of blood vessels. Furthermore, EPCs were found to be a potential choice for venous thrombosis (VT) treatment. MATERIAL/METHODS: EPCs were isolated from human peripheral blood of healthy adults and VT patients. Differently expressed micro(mi)RNAs were examined by quantitative real-time polymerase chain reaction, after which proliferative capacity and migration effect were tested by Cell-Counting Kit 8, scratch wound assay, and transwell assays. Bioinformatic analysis was applied to investigate the potential target messenger ribonucleic acid and a dual-luciferase reporting system was utilized to confirm the binding of miR-22-3p to its target gene. Western blot was carried out to detect candidate protein expression level. Finally, miR-22-3p expression was monitored in VT patients during follow-up to assess its correlation with prognosis of VT. RESULTS: Our data revealed that miR-22-3p was upregulated in EPCs derived from deep VT (DVT) individuals and suppression of miR-22-3p contributed to proliferation and migration of EPCs. In addition, miR-22-3p/onecut 1 (OC1)/vascular endothelial growth factor A (VEGFA) signaling pathway was involved in regulating EPC migration and proliferation. In addition, lower expression of miR-22-3p in DVT patients indicated decreased risk of VT recurrence. CONCLUSIONS: Our results suggest that miR-22-3p regulates OC1/VEGFA signaling and is involved in regulating EPC proliferation and migration. The expression level of miR-22-3p could be monitored to predict DVT patients’ prognosis.